Making it ‘APP’en: service user feedback: developing and implementing a service user APP: reflections from Northern Ireland, England and Scotland. - Westwood, Joanne; Dill, Katharine; Campbell, Anne; Shaw, Alaine (Social Work Education, 2017)
Despite the advent of social media and increasing use of smart phone technology amongst global and UK populations, APP’s for social work remain in their infancy. Several have been developed which focus on the education of social workers and practitioners providing information on specific social work issues, and one we are aware of that explores ethics and values using a games-based approach. In this paper, we discuss the importance of service user perspective in social work practice and how this informed the development of the feedback App. We reflect on developing this instrument using digital technologies which social workers can use to gather anonymous feedback from service users about their experiences of social work interventions. This project, developed in response to demands placed on social work agencies to evidence the effectiveness of service interventions, provide robust data from service users for inspection regimes and sustain service user involvement in improving services. The evaluation model is designed to document the implementation process, exploring what works and what barriers, challenges and lessons were learned by the project team together with how some of the tensions in the process were addressed and resolved.